Video game level design : how to create video games with emotion, interaction and engagement - Salmond, Michael (London, England : Zed Books, 2021)
"Explains what level design is and how to use it to make engaging video games"--
-- 1. What Is Level Design? -- 2. Creating Immersive, Believable Worlds -- 3. Design for Narrative -- 4. Environment Design vs Level Design -- 5. Building Worlds -- 6. Design for Single & Multiplayer -- 7. Level Design is Agile Design -- 8. The Language of Level Design -- 9. Prototyping Level Design -- 10. The Game Is the Level, the Level Is the Game -- 11. Communication and Final Touches -- 12. Where to Next?
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Level design (Computer science); Video games -- Psychological aspects; Computer games design; Electronic books